Faktor-Faktor yang Mempengaruhi Penghentian Prematur Prosedur Audit: Tekanan waktu, Risiko Audit, dan Tindakan Supervisi. - Arne Frans M. Simamora; Deliana; Cris Kuntadi (Cipta Kind Publisher, 2023)
Abstract Premature termination of audit procedures is one of the behaviors that can reduce audit quality. This article aims to determine the effect of the premature termination of audit procedures by conducting a literature study from various studies that have been done. This article reviews the factors that influences premature termination of audit procedures, namely: time pressure, audit risk and supervision. The results of this literature review article are:1) time pressure influences premature termination of audit procedures; 2) audit risk influences premature termination of audit procedures; and 3) supervision influences premature termination of audit procedures.